Hepatitis C Virus Reactivation in Anti-HCV Antibody-Positive Patients with Chronic Hepatitis B Following Anti-HBV Therapies - Yi-Tse Su; Ming-Ling Chang; Rong-Nan Chien; Yun-Fan Liaw (Viruses, 2022)
Background and Aims: Whether hepatitis C virus (HCV) reactivation occurs and how the viral load evolves in anti-HCV antibody-positive chronic hepatitis B (CHB) patients who underwent nucleos(t)ide analogue (Nuc) therapies remain unsolved. Methods: A cohort of 66 such patients was studied. Results: At the start of Nuc treatment (baseline), all patients had detectable hepatitis B virus (HBV) DNA levels (6.05 ± 1.88 log IU/mL), while HCV RNA levels (3.79 ± 1.43 log IU/mL) were detected (i.e., chronic hepatitis C (CHC)) in only 13 patients (19.7%). Following Nuc therapies, HBV DNA levels reached the nadirs at end of therapy (EOT) (6.05 ± 1.88 vs. 0.25 ± 0.99 log IU/mL, p < 0.0001) and relapsed at 6 months after EOT (6mEOT) at a level of 3.45 ± 2.64 log IU/mL compared with EOT (p < 0.0001). Among the 13 CHC patients, a non-significant decrease in HCV RNA was noted at EOT (3.52 ± 1.71 vs. 2.77 ± 2.63 log IU/mL, p = 0.166) but tended to decrease further at 6mEOT (2.77 ± 2.63 vs. 1.89 ± 2.06 log IU/mL, p = 0.063). Two of the thirteen CHC patients showed an increase in HCV-RNA ≥ 1 log10 IU/mL at EOT, and one of the fifty-three patients with undetectable HCV RNA at baseline (i.e., resolved past HCV infection) showed detectable HCV RNA at year 1 (3200 IU/mL) and year 2 (1240 IU/mL) following entecavir therapy. Conclusions: HCV reactivation did occur during HBV suppression, and the rate was 4.5% (3/66), 15.4% (2/13), and 1.9% (1/53), for all patients, CHC patients, and patients with resolved past HCV infection, respectively. The reverse HBV and HCV viral evolutions at 6mEOT indicate that HBV relapse may suppress HCV replication again.